Beyond the Classroom: Enhancing Career Clarity and Preparedness Through Volunteer Psychoeducational Group Facilitation for Behavioral Health Undergraduates - Elizabeth Valenti; Kathleen Downey (Journal of Scholarly Engagement)
This article provides an example of a university faculty member’s reflective practice on how a sense of community was developed within undergraduate college forensic science classrooms. Through reflective practice, I describe a heartwarming situation I experienced and compare it to the literature to help me better understand my contribution to developing a sense of community amongst my students. After identifying and evaluating possible explanations, I decide a positive learning environment is the main contributing factor and provide recommendations for future practice to help other faculty who are interested in creating a similar environment within their own courses.